Structure-activity relationships for analogs of the tuberculosis drug bedaquiline with the naphthalene unit replaced by bicyclic heterocycles. Issue 8 (1st May 2018) - Sutherland, Hamish S.; Tong, Amy S.T.; Choi, Peter J.; Conole, Daniel; Blaser, Adrian; Franzblau, Scott G.; Cooper, Christopher B.; Upton, Anna M.; Lotlikar, Manisha U.; Denny, William A.; Palmer, Brian D.
Graphical abstract: Abstract: Replacing the naphthalene C-unit of the anti-tuberculosis drug bedaquiline with a range of bicyclic heterocycles of widely differing lipophilicity gave analogs with a 4.5-fold range in clogP values. The biological results for these compounds indicate on average a lower clogP limit of about 5.0 in this series for retention of potent inhibitory activity (MIC90 s) against M.tb in culture. Some of the compounds also showed a significant reduction in inhibition of hERG channel potassium current compared with bedaquiline, but there was no common structural feature that distinguished these.